Paleobotani: Dryobalanoxylon, Fosil Kayu Asal Jambi (Paleobotany: Dryobalanoxylon, Fossil Wood Origin Jambi) - Andianto Andianto; Agus Ismanto; Ratih Damayanti (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Jambi Province is known as an area with abundant source of geological diversity (Geodeversity), including fossil woods. Specimen of Fossil wood from Merangin District-Jambi was observation its anatomical structures on thin slices of cross, radial and tangential-section  using Carl Zeiss-Axio Imager A1m microscope. The description of wood anatomical structures referred to the International Association of Wood Anatomists (IAWA) list of microscopic features for hardwood identification. The age estimate of fossil wood is based on geological map (scale 1: 100.000) of Sarolangun sheet, Sumatra. The anatomical structures of the fossil wood are as follow: vessel exclusively solitary, simple perforation plates, intervessel pits alternate, very thick fibre wall, apotracheal parenchyma diffuse-in-aggregates, paratracheal parenchyma vasicentric, axial canals in long tangential lines, prismatic crystal in chambered axial parenchyma cells, and silica bodies present in ray cells and axial parenchyma cells. The anatomical structures mentioned are similar to Kamper/Kapur wood species (Dryobalanops sp.) which it is member of Dipterocarpaceae family, with the result that  this fossil is Kamper wood (Dryobalanoxylon sp.). Based on age analysis through the geological map, it is estimated that this fossil wood was formed between 3.60 and 2.58 million BP (Before Present), which was between the late Pliocene and the early Plistocene era.